Individual Resilience and Protective Mental Health: The Role of Psychological Resilience - Nurten Elkin; Ayşe Mücella Soydan (İstanbul Gelişim Üniversitesi Sağlık Bilimleri Dergisi, 2026)
This review examines the concepts of psychological resilience and preventive mental health, and their roles in individuals' mental health protection and improvement processes. Psychological resilience represents individuals' capacity to adapt to stressful and challenging life conditions, while the preventive mental health approach aims to strengthen individuals' internal resources and environmental support systems. Literature findings show that psychological resilience is effective not only in preventing mental health problems but also in increasing individuals' life satisfaction and subjective well-being. This highlights the importance of empowering and preventive approaches in addition to risk-focused approaches in mental health practices. It is emphasized that individual characteristics, social support, family, and environmental factors are decisive in the development of psychological resilience; and that the interaction between preventive mental health and psychological resilience plays a crucial role in protecting mental health at both individual and societal levels. The study emphasizes the importance of integrating programs that support psychological resilience into education, work, and community-based mental health services, and highlights the need for longitudinal and experimental studies in future research. This review demonstrates that psychological resilience is a fundamental building block in the preventive mental health perspective and contributes to strengthening mental health at both individual and societal levels.